DARA SHIKOUH AND HIS MODEL OF INTER-RELIGIOUS UNDERSTANDING: AN ASSESSMENT - MIR, JAVAD AHMAD; GN, KHAKI (Innovare Journal of Social Sciences, 2022)
Prince Muhammad Dara Shikouh held two-sided position in Indian history as a political figure and as an intellectual personality. However, his political carrier was short and shadowed with failures. However, his contribution toward cultural legacy of Indian intellectual history is profound and amazing especially in the field of inter-religious dialogue. He was the icon of cultural pluralism. Religious exclusim, radical ideology, religious fundamentalism, and communal forces have shadowed the ethos of cultural pluralism and secular tendencies of contemporary world, hence put the peace of the planet in threat. Before Dara Shikouh, many saints, reformers, and liberal ideologists tried to promote mutual cooperation and peaceful coexistence between adherents of various religions, cultures, and ethnicities, but Dara’s efforts were unique in various manners in this regard. He has given a model of religious toleration, which was short lived but still has relevance and can be helpful in many ways in the present times for the promotion of socio-religious harmony between Muslims and Hindus. The present study will try to examine and explore the contribution of Dara Shikouh in the promotion of inter-religious understanding in Indian context through historical analysis of his thought.